Penerapan Contextual Teaching And Learning (CTL) pada Materi Model Atom dengan Mengangkat Fenomena Kompor Gas Elpiji dalam Mata Kuliah Fisika Modern - Amin, Ahmad; Yuneti, Armi (LP4MK STKIP PGRI Lubuklinggau, 2025)
The Modern Physics course discusses basic concepts such as relativity, quantum, and atomic structure, which form the basis of today's technology. One of the important early topics, namely the atomic model, is often difficult for students to understand because it is abstract and not immediately apparent. The Contextual Teaching and Learning (CTL) approach provides a solution by linking academic material to real phenomena that are close to everyday life. One example is the color of the flame on a propane gas stove, which reflects electron transitions and the light spectrum. By utilizing this phenomenon as a learning context, students can understand the concept of the atomic model in a more concrete, meaningful, and applicable way. The purpose of this study was to measure students' interest in learning after the application of Contextual Teaching and Learning (CTL) in the Atomic Model Material by raising the phenomenon of LPG gas stoves. The research method used was descriptive, and the data analysis used was quantitative descriptive analysis of learning interest after learning. The subjects of this study were 15 fifth-semester students in the 2025/2026 academic year from the Physics Education Study Program at PGRI Silampari University. Data collection techniques used questionnaires, and the data collection instrument was a questionnaire on learning interest. The research results were obtained after applying CTL to atomic model material by raising the phenomenon of LPG gas stoves. The average student learning interest questionnaire score reached 73.5, with a classical percentage score of 93.3%, so it can be concluded that the application of the CTL model to atomic model material by raising the phenomenon of LPG gas stoves made student learning interest very good.